2018
DOI: 10.1016/j.tra.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Port infrastructures and trade: Empirical evidence from Brazil

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints-eprint.ncl.ac.uk Bottasso A,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 57 publications
3
28
0
2
Order By: Relevance
“…Consequently, the results confirm the value of interregional infrastructure projects like the TEN-T initiative that can improve transport conditions in important transit countries. Additionally, the estimation results suggest that infrastructure improvements exert a greater impact on exports than on imports, a similar result to Francois and Manchin (2013) or Bottasso et al (2018). This highlights the importance of creating infrastructural conditions which enable companies to export their products more conveniently and e ciently.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Consequently, the results confirm the value of interregional infrastructure projects like the TEN-T initiative that can improve transport conditions in important transit countries. Additionally, the estimation results suggest that infrastructure improvements exert a greater impact on exports than on imports, a similar result to Francois and Manchin (2013) or Bottasso et al (2018). This highlights the importance of creating infrastructural conditions which enable companies to export their products more conveniently and e ciently.…”
Section: Discussionmentioning
confidence: 66%
“…Blonigen and Wilson (2008) also find that port e ciency significantly increases trade volumes between ports in the United States and ports of other countries. For Brazil, Bottasso et al (2018) show that an increase in port infrastructure strongly increases exports and that port infrastructure can also have positive, but less pronounced e↵ects on imports. Clark et al (2004), as well as Márquez-Ramos et al (2011), estimate that maritime transport costs decrease with a better port infrastructure, and that transport costs (in a separate analysis) decrease bilateral maritime trade flows.…”
Section: N S T I T U T Eo Ft R a N S P O R Te C O N O M I C Smünstementioning
confidence: 95%
“…Hwang et al (2017) have also identified the contribution of logistics industry to national economic growth. By studying the Brazilian exports, Bottasso et al (2018) found positive association between port infrastructures and export volume and that the development of other types of transport infrastructure can reinforce this relationship. In general, since the physical infrastructures and the related technologies and services of a country are publicly accessible by all of its trading businesses, the transport logistics development targeting intra-FTA trade growth can promote the flows of extra-FTA trade.…”
Section: Hypothesis Developmentmentioning
confidence: 91%
“…Recurrent arguments include the fact that sea-land transshipment may generate economies of scale while increasing the number of destinations and shipping frequency, thereby opening new markets to ports beyond their traditional hinterlands (van Klink and van den Berg, 1998). While the influence of physical infrastructure interconnection cannot be ignored (Bottasso et al, 2018), most studies focus more on the role of vertically integrated actors in establishing intermodal services (Franc and Van der Horst, 2010;Notteboom et al, 2017) and so-called dry ports (inland) to relieve seaports from congestion and enhance distribution systems, among other goals (Roso et al, 2009). Hinterland delineation, a longstanding issue in transport studies, recently improved but tended to ignore shipping linkages per se (Halim et al, 2016;Tiller and Thill, 2017;Zanon Moura et al, 2017;Jung et al, 2018).…”
Section: Intermodal Transport and Port Citiesmentioning
confidence: 99%